PERANAN PENDIDIKAN LUAR SEKOLAH DALAM RANGKA MITIGASI BENCANA - Vevi Sunarti (Universitas Negeri Padang, 2014)
The role of non formal education oriented toward change and micro-social behavior in the short term. Disaster mitigation is a series of efforts to reduce disaster risk, either through physical development or awareness and increased capacity in dealing with hazards disaster. Disaster education is one way of mitigation that can be done in the community such as the institute courses, learning centers (PKBM), and other study groups. Disaster education to the community is an important part that should not be overlooked. Public awareness in disaster prone areas is absolutely necessary, because without awareness, attitude and character of disaster conscious will not grow. So that when disaster strikes all the people will not be confused, panic, because it has been studied disaster education.